Sara's face - Burgess, Melvin (New York : Simon & Schuster Books for Young Readers, 2007)
Seventeen-year-old Sara wants so much to be famous that when a legendary, plastic-surgery-addicted rock star offers to take her under his wing and pay for her to have surgery too, she jumps at the chance despite her misgivings.
Keywords: Identity -- Fiction; Emotional problems -- Fiction; Face -- Fiction; Surgery, Plastic -- Fiction; Fame -- Fiction; England -- Fiction